Invisible Ethics: The Problem of Anonymity on the Internet - Abreu Ladeira da Costa e Silva, Miguel (Université d'Ottawa / University of Ottawa, 2020)
This thesis aims to shed some light on the way anonymity affects behavior online, as well as the moral implications this influence supposes for internet users. We do this in three chapters, each dedicated to a specific aspect that might be problematic, and look at the technical aspects of the influence of anonymity, as well as the psychological aspects of this influence. We begin by analyzing anonymity as a tool that gives rational actors an advantage over their peers. We then gage the extent to which it constitutes a situational force, and how it coordinates with other situational forces within the online environment. Finally, through an evaluation aided by moral psychology and the literature in ethics, we use a situationist approach to identify the two main ways in which we believe anonymity affects moral behavior in the internet.
Keywords: Anonymity; Internet; Ethics; Situational forces; Identity; Behavior